2021
DOI: 10.1016/j.crphar.2021.100047
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between anticancer drugs and mitochondrial functions

Abstract: Chemotherapy is an important component of cancer treatment, which has side effects like vomiting, peripheral neuropathy, and numerous organ toxicity but the most significant outcomes of chemotherapy are cognitive impairment, which is mainly referred to as chemobrain or CICI (chemotherapy-induced cognitive impairment). It is characterized by difficulty with language, concentrating, processing speed, learning, and memory, as it affects the hippocampus areas of the brain. Mitochondrial dysfunction and oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 126 publications
1
10
0
1
Order By: Relevance
“…In contrast, toxic properties, particularly doses of mitochondrial-mediated programmed cell death, affect not only cancer cells or parasitic cells but also normal host cells. It has been reported that chemotherapeutic drugs can cause collateral damage to normal cells, such as the occurrence of chemobrain or CICI (chemotherapy-induced cognitive impairment) due to mitochondrial dysfunction and oxidative stress [ 18 ]. Therefore, the risk/benefit ratio of the administration of drugs, chemicals, and pharmaceuticals should be considered and balanced.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, toxic properties, particularly doses of mitochondrial-mediated programmed cell death, affect not only cancer cells or parasitic cells but also normal host cells. It has been reported that chemotherapeutic drugs can cause collateral damage to normal cells, such as the occurrence of chemobrain or CICI (chemotherapy-induced cognitive impairment) due to mitochondrial dysfunction and oxidative stress [ 18 ]. Therefore, the risk/benefit ratio of the administration of drugs, chemicals, and pharmaceuticals should be considered and balanced.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Among them, mitochondrial dysfunction is reported to be significant pathogenesis of CIPN, which corresponds to the clinical manifestations. 11 15 …”
Section: Mitochondrial Dysfunction In Cipnmentioning
confidence: 99%
“…After ionizing radiation, persistent oxidative stress characterized by mitochondrial dysfunction and upregulation of the NADPH oxidase complex is observed [173]. Likewise, chemotherapeutic drugs such as platinum-based drugs, adriamycin, and cyclophosphamide, impair the normal mitochondrial function and antioxidant response that increases superoxide anion [174].…”
Section: Oncologymentioning
confidence: 99%